EVALUATION OF SERUM INTERLEUKINS 1 AND 10 IN TYPE 2 DIABETES MELLITUS SUBJECTS IN BENIN CITY - Digban, Awharentomah Kester; Adu, Matthew Eturhobore; Adenuga, Mary Abiodun (FUDMA JOURNAL OF SCIENCES, 2023)
Diabetes mellitus is a metabolic and endocrinological disease that results in hyperglycemia as a result of either insulin absence or non-responsiveness of insulin receptors. Interleukins have been implicated in the pathogenesis of diabetes mellitus. This study sought to evaluate serum interleukin-1 and 10 in diabetes mellitus. A total of three hundred subjects comprising of one hundred and eighty diabetes mellitus and one hundred and twenty apparently healthy subjects were recruited. Of the one hundred and eighty diabetes mellitus is made of 41.67% male and 58.33% females. Venous blood samples were collected into fluoride oxalate and plain containers and allowed to clot and the serum harvested. Glucose, IL-1 and IL-10 were estimated using standard methods. Statistical package for social sciences (SPSS) Chicago, USA, version 21 was used for data analysis.  Our results show that IL-1 was significantly higher while IL-10 was observed to be significantly lower in diabetes mellitus when compared with apparently healthy subjects. It was observed that interleukin -1 and interleukin -10 were positively associated when correlated. Conclusively, interleukins are important in the pathogenesis of diabetes mellitus and should be evaluated for proper understanding of the pathogenesis of diabetes mellitus.
Keywords: Interleukin-1; Interleukin -10; Diabetes mellitus; Cytokine; Inflammation